Peran PB Djarum dalam Peningkatan Prestasi Olahraga Bulu Tangkis Indonesia, 1969-2019 - Sabathani, Rahel; Ridhoi, Ronal (Perkumpulan Program Studi Sejarah Se-Indonesia, 2025)
This research aims to describe the role of the badminton club in Indonesia, namely PB Djarum, in improving Indonesia's achievements in the national and international arena from 1969 to 2019. Badminton has a place in society just like the much-loved sport of football. The very high development of badminton is influenced by the mushrooming of clubs and the love of the Indonesian people for this sport. From this, the problem to be studied is how PB Djarum was formed and what factors strengthened PB Djarum for Indonesian sports achievements from 1969 to 2019. This research method will use historical methods, namely topic search, heuristics, criticism, interpretation, and then historiography. The results of this paper discover how PB Djarum was formed in 1969 and the role of PB Djarum in improving quality, namely by developing management of infrastructure, players and even coaches. Not only that, PB Djarum's achievements have also increased after experiencing a decline.